Detention and Torture Centers in Latin American Dictatorships: Places of Subjective and Social Reconfiguration - Santos-Herceg, J (Taylor and Francis, 2021)
The aim of this work is to show that “Detention and Torture Centers” were the places from which Latin American dictatorships developed and implemented the project of a complete subjective and social reconfiguration. Torture was a central element in achieving this goal. It was not just another phenomenon that took place during imprisonment, but was a key element in understanding the functioning and importance of these places. This chapter seeks to establish that torture was a fundamental tool in the project of subjective and social reconfiguration of Latin America’s dictatorships. © 2021 Taylor and Francis.